Family Functionality, Self-esteem and Depression in Higher Education students in the city of Tacna – 2020 - Nuñez Delgado, Rocio del Pilar (2021)
Depression is a disease, a public health problem and is related to self-esteem, which is the degree of self-worth, which in turn influences family functionality, as an important key to the development of its members; The research is cross-sectional and confirmatory, of the non-probabilistic sample of 115 higher education students from the city of Tacna to determine the adjustment indices of the explanatory model of the Family Functionality Scale based on Selfesteem and Depression; which X2 / gl = 27.352, CFI = 0.086, GFI = 0.729, were not acceptable, only SRMR = 0.3798 was adequate, but globally we can conclude that the fit indices of the explanatory model between family functionality related to self-esteem and it is related Depression is not appropriate in higher education students from Tacna.